2009
DOI: 10.1002/clen.200900090
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of Cd(II), Ni(II) and Pb(II) from Aqueous Solution by Dried Biomass of Aspergillus niger: Application of Response Surface Methodology to the Optimization of Process Parameters

Abstract: In this study, the biosorption of Cd(II), Ni(II) and Pb(II) on Aspergillus niger in a batch system was investigated, and optimal condition determined by means of central composite design (CCD) under response surface methodology (RSM). Biomass inactivated by heat and pretreated by alkali solution was used in the determination of optimal conditions. The effect of initial solution pH, biomass dose and initial ion concentration on the removal efficiency of metal ions by A. niger was optimized using a design of exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 62 publications
5
32
1
Order By: Relevance
“…2 shows that the isothermal data better conformed to Freundlich equation. The maximum capacity (q m , mmol/g) was found to be 0.0769 mmol/g and is significantly higher than those reported in reference [2] and references therein. Accordingly, the nano magnetite particles could serve as an adsorbent to remove nickel ions from aqueous solutions.…”
Section: Adsorption Isothermscontrasting
confidence: 62%
See 1 more Smart Citation
“…2 shows that the isothermal data better conformed to Freundlich equation. The maximum capacity (q m , mmol/g) was found to be 0.0769 mmol/g and is significantly higher than those reported in reference [2] and references therein. Accordingly, the nano magnetite particles could serve as an adsorbent to remove nickel ions from aqueous solutions.…”
Section: Adsorption Isothermscontrasting
confidence: 62%
“…Presently, considerable attention has been given to the methods for their removal from industrial wastewaters. Conventional methods for removing heavy metals ions form aqueous solutions principally include chemical precipitation, ion-exchange, reverse osmosis, and adsorption (bioadsorption) [1,2]. Although the effectiveness of these processes has been sufficiently proven, they present some inconveniences and limitations due to high energy requirements, incomplete metal removal, and a large amount of sludge production [3].…”
Section: Introductionmentioning
confidence: 99%
“…The RSM consist of a group of empirical techniques devoted to the evaluation of the relationship existing between the independent variables and measured responses [34].…”
Section: Box-behnken Methodology For Dye Decolorizationmentioning
confidence: 99%
“…A similar results were observed with Fan et al [33], who reported that maximum biosorption capacity for Zn(II) by Penicillium simplicissimum was achieved at pH 6.0. On the other hand, Vullo et al [34] concluded that the optimum pH for Zn(II) was achieved at pH 7.5 with Pseudomonas veronii 2E, Amini and Younesi [35] found a biosorption of Cd(II) at pH 6.01 for Asperigillus niger.…”
Section: Effect Of Phmentioning
confidence: 97%